THE IMPLEMENTATION OF HIGHER-ORDER THINKING SKILLS (HOTS) IN TEXT-BASED LEARNING AT SDN BANYURIP 3 SAMBUNGMACAN - Agustina, Tiya; Oktavia, Wahyu; Inderasari, Elen (UIN Sunan Kalijaga Yogyakarta, 2020)
Current learning must be directed at higher-order thinking skills and text-based. This condition certainly requires an adaptation process that is not easy. Based on these problems, this study aims to describe the implementation of Higher Order Thinking Skills (HOTS) in text-based learning at State Elementary School of Banyurip 3 Sambungmacan or called SDN Banyurip 3 Sambungmacan. This research is descriptive qualitative research. Data collection techniques used in this study, namely observation, interviews, and documentation. The documents used in this study are in the form of a syllabus, lesson plans, and photos of the learning process. Data validity is done using the triangulation of sources and methods. The data analysis techniques used include data collection, data reduction, data presentation, and concluding. The formulation of the problems examined in this study shows how (1) HOTS planning in text-based learning (2) HOTS implementation in text-based learning (3) HOTS assessment in text-based learning (4) how the constraints experienced in the application of HOTS in text-based learning. The results showed that the planning and implementation of text-based learning had gone well. The selection of learning components has been able to build a HOTS learning atmosphere. Text-based learning assessments in elementary schools have used authentic assessments. Obstacles experienced by teachers in the process of text-based learning include; arrange the right plan, the difficulty in dividing the time allocation, the selection of the right media, the suitability of learning resources with student characteristics, the integration of interesting learning methods.